The Effect of Massage until Completion of Fetal Period on Reflexes of Preterm Neonates - Mansoureh Mokaberian; Shamsollah Nooripour (University of Tehran, 2018)
Reflexes are body automatic and involuntary responses to a variety of stimuli such as pressure, sound and tactile stimulation which are used as means to determine the level of neurological maturation and to diagnose central nervous system disorders. The aim of this study was to investigate the effect of mothers' tactile kinetic stimulations on reflex state of preterm neonates. For this purpose, 40 infants and mothers were purposively selected from infants hospitalized in neonatal ward of Amiralmomenin hospital in Semnan city during one to two months and were randomly divided into experimental and control groups. Then, mothers of experimental group conducted tactile kinetic stimulations on their infants until the completion of fetal period (40 weeks of gestation) 3 times a day, 20 minutes each time whereas the control group received only the usual care. Neonatal Behavioral Assessment Scale was used to evaluate reflex state of neonates before and after the intervention. The results of mixed ANOVA showed that although reflexes of premature neonates in the experimental group improved more than the control group, this increase was not significant (P≥0.05). However, given these results, it can be said that tactile kinetic stimulations can be a solution to improve the reflex state of preterm neonates and more time frame is probably required to reveal the beneficial effects of intervention.